1993
DOI: 10.1007/bf01973305
|View full text |Cite
|
Sign up to set email alerts
|

Formation of N-methyl protoporphyrin in chemically-induced protoporphyria

Abstract: 1-[4-(3-Acetyl-2,4,6-trimethylphenyl)-2,6-cyclohexanedionyl]-O-eth yl propionaldehyde oxime (for short ATMP) is a novel porphyrogenic agent causing hepatic protoporphyria in the mouse. Mice given a single dose of the drug showed 24 h later a 70% inhibition of liver ferrochelatase and marked accumulation of protoporphyrin. These changes were not seen in similarly treated rats, guinea pigs, hamsters or chick embryos. A green pigment was isolated from the liver of mice treated with ATMP and identified by its elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Griseofulvin, ethyl-DDC, and TMDQ are metabolized by CYP enzymes, leading to the formation of N-alkyl protoporphyrins which covalently bind to ferrochelatase enzyme and inactivate it (De Matteis and Marks 1996;Halpert et al 1994). Similar mechanisms are also suspected for AIA and ATMP (Frater et al 1993;De Matteis and Marks 1996). Especially ethyl-DDC is a highly potent ferrochelatase inhibitor and cellular heme depletor (Halpert et al 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Griseofulvin, ethyl-DDC, and TMDQ are metabolized by CYP enzymes, leading to the formation of N-alkyl protoporphyrins which covalently bind to ferrochelatase enzyme and inactivate it (De Matteis and Marks 1996;Halpert et al 1994). Similar mechanisms are also suspected for AIA and ATMP (Frater et al 1993;De Matteis and Marks 1996). Especially ethyl-DDC is a highly potent ferrochelatase inhibitor and cellular heme depletor (Halpert et al 1994).…”
Section: Discussionmentioning
confidence: 94%
“…It would therefore be prudent when dealing with xenobiotics in which porphyrinogenicity depends upon interaction with P450 enzymes and N-alkylPP formation to supplement animal data with studies in human liver microsomes and cDNAexpressed individual P450 enzyme preparations. This would be particularly important where xenobiotics are shown to be porphyrinogenic due to the production of N-alkylPPs in the livers of some animal species but not others (Frater et al, 1993).…”
Section: Human P450 Sources Of N-alkylpp After Interaction With Xenobmentioning
confidence: 99%
“…In the case of xenobiotics, which owe their porphyrinogenicity to mechanism-based inactivation of selective P450 enzymes with formation of N-alkylPPs, the problem stems, in part, to differences in the P450 enzymes between animals and humans. This is a particular problem when a xenobiotic is found to be porphyrinogenic in one species but not in others (Frater et al, 1993). Therefore, an understanding of the human P450 enzymes targeted by these xenobiotics is required to establish whether porphyria elicited in animals is likely to occur in humans.…”
mentioning
confidence: 99%
“…In other laboratory species such as mice, rats and genetically engineered (ferrochelatase deficient) mice, such changes have been described as well after drug-treatment (Zaki et al, 1973;Matilla and Molland, 1974;Cantoni et al, 1983;Tutois et al, 1991;Frater et al, 1993;Smith et al, 1997). However, in a rat study carried out in our laboratory with the same drug candidate as used in the dog study, no lesions indicative for porphyria were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic animals mainly develop congenital and hereditary porphyria (With, 1980) whereas in laboratory animals (rats and mice) drug-induced porphyria have been described in literature (Matilla and Molland, 1974;Gralla et al, 1977;Cantoni et al, 1983;Frater et al, 1993;Smith, 1997). For dogs, information about experimentally induced porphyria is scarce and not of recent date (Stokvis, 1895;Zaki et al, 1973;Stejskal et al, 1975).…”
Section: Introductionmentioning
confidence: 99%